Performance of Sub-surface Drainage under ORP trial in Sandy Loam Sodic Soils with High Water Table Condition - Sharma, R K; Verma, S K; Tiwari, S C (Journal of Agricultural Engineering, 2008)
A sub-surface drainage system using corrugated perforated PVC pipe was installed in a plot area of 33m x 60 m size sub-surface with 100 m lateral drains and 100 m collector drain having surrounded by a 5 cm thick envelope of 2-6 mm sized mineral components. The lateral drains were installed at 18m spacing and 0.6 m depth and collector drain was at a depth of 0.7 m. The study revealed that provision of sub surface drainage in sodic sandy loam soils improve the yields of Til (TKG- 55), Wheat (HD -4672), Pearl millet (JVB - 3) and Bengal Gram (PG - 5) over undrained condition by 15, 12, 19 and 18 percent, respectively.